2012
DOI: 10.1016/j.neuropharm.2012.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human D398N single nucleotide polymorphism on intracellular calcium response mediated by α3β4α5 nicotinic acetylcholine receptors

Abstract: The human CHRNA5 D398N polymorphism (rs16969968) causes an aspartic acid to asparagine change in the nicotinic acetylcholine receptor (nAChR) α5 subunit gene. The N398 variant of CHRNA5 is linked to increased risk for nicotine dependence. In this study, we explored the effect of the CHRNA5 D398N polymorphism on the properties of human α3β4* nicotinic acetylcholine receptors in human embryonic kidney (HEK) cells. Addition of either D398 or N398 variant of α5 subunit in the α3β4* receptor did not affect total [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 82 publications
(106 reference statements)
5
48
1
Order By: Relevance
“…This hypothesis is supported by large GWAS meta-analyses and in vitro studies that have characterized the function of 398 D4N and behavioral studies of α5 in animal models (Bailey et al, 2010;Bierut et al, 2008;Fowler et al, 2011;Frahm et al, 2011;Jackson et al, 2010;Kuryatov et al, 2011;Saccone et al, 2010;Tammimaki et al, 2012;Tobacco and Genetics Consortium, 2010). The CHRNA5 risk allele, rs16969968*A (398N), encodes a protein that forms nACh receptors with lower activity in several in vitro paradigms (Bierut et al, 2008;Kuryatov et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…This hypothesis is supported by large GWAS meta-analyses and in vitro studies that have characterized the function of 398 D4N and behavioral studies of α5 in animal models (Bailey et al, 2010;Bierut et al, 2008;Fowler et al, 2011;Frahm et al, 2011;Jackson et al, 2010;Kuryatov et al, 2011;Saccone et al, 2010;Tammimaki et al, 2012;Tobacco and Genetics Consortium, 2010). The CHRNA5 risk allele, rs16969968*A (398N), encodes a protein that forms nACh receptors with lower activity in several in vitro paradigms (Bierut et al, 2008;Kuryatov et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…In this region the 398 th residue of nAChR hα5 subunit (i.e., D398), equivalent to the 471 st residue of nAChR hα2 subunit (i.e., E471) (Fig. 1; arrow mark), has drawn great attention for its role in ND and other diseases (Frahm et al, 2011; George et al, 2012; Hong et al, 2010; Kuryatov et al, 2011; Li et al, 2011; Tammimaki et al, 2012; Thorgeirsson et al, 2008). The N398 residue (i.e., the mutant/risk allele) of nAChR α5 subunit is predicted to alter the structure of intracellular vestibule/cytoplasmic portals of α3β4α5-nAChR (Frahm et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The D398N variation in nAChR α5 subunit commonly associated with ND and other diseases is mapped to the cytoplasmic vestibular regions (i.e. MA stretch) and is shown to modulate function of nAChRs both in vitro and in vivo (Frahm et al, 2011; George et al, 2012; Kuryatov et al, 2011; Tammimaki et al, 2012). In these studies it is shown that D398N variation in nAChR α5 subunit decreases the agonist response of α4β2- or α3β4-nAChRs (George et al, 2012; Kuryatov et al, 2011) or doesn’t affect the pharmacology of α3β4-nAChR activation (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro transfection studies have shown that introduction of the a5 subunit reduces the maximal a3b4* nAChR response to agonist activation and shifts the downstream signaling pathways (Tammimäki et al, 2012). Introduction of the D398N a5 subunit variant, which is linked to increased risk for nicotine dependence, further decreases agonist response at the a3b4* nAChR (Frahm et al, 2011;Tammimäki et al, 2012).…”
Section: Medial Habenula-interpeduncular Nucleusmentioning
confidence: 99%
“…In vitro transfection studies have shown that introduction of the a5 subunit reduces the maximal a3b4* nAChR response to agonist activation and shifts the downstream signaling pathways (Tammimäki et al, 2012). Introduction of the D398N a5 subunit variant, which is linked to increased risk for nicotine dependence, further decreases agonist response at the a3b4* nAChR (Frahm et al, 2011;Tammimäki et al, 2012). A transgenic mouse model, Tabac, in which b4 subunit overexpression enhances a3b4* nAChR levels, has been shown to increase aversion to nicotine, an effect that is reversed by lentiviral transfection of the D398N a5 subunit into the MHb (Frahm et al, 2011).…”
Section: Medial Habenula-interpeduncular Nucleusmentioning
confidence: 99%